2018
DOI: 10.18203/2349-2902.isj20183196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chewing gum on bowel motility in post operative patients following abdominal surgery: a clinical outcome based study

Abstract: Background: One very important complication of abdominal surgeries is postoperative ileus which results in severe patient discomfort, prolonged hospitalization, and enhanced treatment cost. This study was conducted with an aim to analyze the clinical outcome of effect of chewing gum mainly to avoid post-operative paralytic ileus in post-operative patients of abdominal surgeries.Methods: In this study total 200 patients were included, 100 were cases and remaining were controls. The cases were given chewing gum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…When the discharge times of patients were compared, it was determined that discharge times of the experimental group patients were 34.5 hours earlier then the control group patients (Table 3). In a study by Kumar et al (2018) with patients who had undergone abdominal surgery, the average hospital stay was determined to be 11.9 days for the gum-chewing group, while it was 12.6 days for the non-gum-chewing group, which shows similar findings to ours.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…When the discharge times of patients were compared, it was determined that discharge times of the experimental group patients were 34.5 hours earlier then the control group patients (Table 3). In a study by Kumar et al (2018) with patients who had undergone abdominal surgery, the average hospital stay was determined to be 11.9 days for the gum-chewing group, while it was 12.6 days for the non-gum-chewing group, which shows similar findings to ours.…”
Section: Discussionsupporting
confidence: 84%
“…Factors such as fluid-electrolyte imbalance, delayed feeding, the use of general anesthetics and narcotic analgesics, and an increase in post-operative sympathetic activity due to stress cause abdominal distention. Stressors such as post-operative pain, suppressing the urge to defecate, and the use of bedpans cause stress responses, and as a result, can cause abdominal distention (Asao et al, 2002;Kumar, Kumari, Kumar, & Raj, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[ 142 143 ] Another meta-analysis of 12 studies and other RCTs have found the results to be equivocal (LOE- Low to Moderate). [ 144 145 146 147 ]…”
Section: Adult Sectionmentioning
confidence: 99%